2019
DOI: 10.3390/ma12081247
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate Resistance of Recycled Aggregate Concrete with GGBS and Fly Ash-Based Geopolymer

Abstract: There is a constant drive for the development of ultra-high-performance concrete using modern green engineering technologies. These concretes have to exhibit enhanced durability and incorporate energy-saving and environment-friendly functions. The object of this work was to develop a green concrete with an improved sulfate resistance. In this new type of concrete, recycled aggregates from construction and demolition (C&D) waste were used as coarse aggregates, and granulated blast furnace slag (GGBS) and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 62 publications
1
34
0
1
Order By: Relevance
“…For example, Somna et al (39) found better results for 100% RCA concrete than for control concrete when 50% of bagasse ash was used as partial replacement of cement. Similar results regarding the benefit of using supplementary cementitious materials (SCM) in RAC are reported in several other studies (40)(41)(42)(43)(44)(45). All these results are explained by the reduction in the porosity that SCMs provide to the RAC matrix.…”
Section: Introductionsupporting
confidence: 87%
“…For example, Somna et al (39) found better results for 100% RCA concrete than for control concrete when 50% of bagasse ash was used as partial replacement of cement. Similar results regarding the benefit of using supplementary cementitious materials (SCM) in RAC are reported in several other studies (40)(41)(42)(43)(44)(45). All these results are explained by the reduction in the porosity that SCMs provide to the RAC matrix.…”
Section: Introductionsupporting
confidence: 87%
“…The increase in the carbonation depth observed in samples containing RCA could be attributed to the higher permeability of RCA due to the presence of old mortar adhering to the NA and the old interfacial transition zone (ITZ) [ 105 ]. The geopolymer RCA, with a higher content of granulated blast furnace slag, had a lower mass loss and a higher residual compressive strength after the sulfate exposure [ 106 ]. The results indicate a direct influence between the percentage of aggregate used in the GC mixes and the level of corrosion that all the specimens present in both the control medium and the aggressive medium.…”
Section: Resultsmentioning
confidence: 99%
“…Geopolymers are a representative example of an admixture that may be used as an AAM. Xie et al [11] experimentally verified that GGBFS-and FA-based geopolymers can provide the excellent sulfuric acid resistance of recycled concrete. AAMs, however, are not yet used in the field due to their fast setting time, large shrinkage, and high unit price.…”
Section: Introductionmentioning
confidence: 99%